A coupled hydraulic–thermal dynamic model for the steam network in a heat–electricity integrated energy system. (15th January 2023) - Yang, Weijia; Huang, Yuping; Zhao, Daiqing
Abstract: Steam is the most common heat support medium in an industrial park's heat–electricity integrated energy system (HE-IES). The steam network (SN) has excellent time delays and heat storage capacity compared to the grid. However, regarding the HE-IES scheduling, previous studies ignored the dynamic delay characteristics of the hydraulic–thermal calculation processes in the SN and the time delays between the SN and the grid when they were operated concurrently. Thus, this paper proposes an improved method of characteristics to incorporate the dynamic hydraulic–thermal processes and quantify the dynamic offsets. To solve the time asymmetry problem associated with the grid, the SN is modeled by a thermal -electrical analogy model and graph theory. The effectiveness of the proposed model was verified by actual SN operating data, and less than 9% relative error between the model outputs and actual results was obtained. The model can satisfy the HE-IES operation requirements with high accuracy. Moreover, in contrast to a thermodynamic process, the hydraulic process can be regarded as a transient process. A generic delay time–distance formula is fitted and applied in the expression of the thermodynamic processes to better improve the HE-IES operations. Highlights: A hydro-thermal coupled dynamics model of an integrated thermal network is proposed based on the method of characteristics. Dimensionless inertia factors are used to simplify the hydro-thermal coupling characteristic line meshes. The shortest topological sequence of a regional thermal network is obtained to free up computational space. An equation relating the disturbance distance and the thermal delay response time is obtained by quantitative analysis. The asymmetric scheduling issue of the integrated energy system is solved.